Skrining Masalah Kesehatan dan Penyuluhan Kesehatan Pada Lansia di Panti Wreda GKJ Gondokusuman Yogyakarta - Masta Hutasoit; Dwi Yati; Ferianto; Yanita Trisetiyaningsih; Khristina Dias Utami (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2024)
The elderly are the population aged 60 years and over. Due to the aging process, the elderly often experience physiological function disorders that interfere with their health and most often cause degenerative diseases. Diseases that are often complained of by the elderly such as heart and blood vessel disease, cancer, diabetes mellitus and others. The results of population projections for 2010-2035 estimated the number of elderly people at 10% of the population. It is stated that Indonesia is experiencing an ageing period.  The purpose of this service is to check the health of the elderly in Pantri Wreda Gondokusuman and health counseling to 10 elderly people. The activity was carried out on April 16, 2023. The results of health checks include blood pressure checks found as much as 60% have hypertension, blood sugar checks found 60% normal, uric acid the majority of elderly people experience high uric acid by 70%. After the health check was completed, it was continued with health counseling with the theme of preventing vascular disease. Pre-test results before counseling 60% of knowledge is lacking and 40% is sufficient. After education 40% of knowledge is in the good category and 50% in the sufficient category and 10% in the insufficient category. It is hoped that the elderly will be able to regularly check their health and maintain a healthy lifestyle so that the elderly can live optimally.